Impact of dietary changes on retinal neuronal plasticity in rodent models of physical and psychological trauma - Patel, Mital Y.; Yang, Ruoting; Chakraborty, Nabarun; Miller, Stacy-Ann; DeMar, James C.; Batuure, Andrew; Wilder, Donna; Long, Joseph; Hammamieh, Rasha; Gautam, Aarti (Frontiers in Genetics, 2024)
Blast injury has been implicated as the major cause of traumatic brain injury (TBI) and ocular system injury, in military operations in Iraq and Afghanistan. Soldiers exposed to traumatic stress also have undiagnosed, chronic vision problems. Here we hypothesize that excessive intake of ω-6 fatty acid linoleic acid (LA) and insufficiency of dietary long chain ω-3 polyunsaturated fatty acids (PUFAs, e.g., docosahexaenoic acid; DHA) would dysregulate endocannabinoid-mediated neuronal plasticity and immune response. The study objective was to determine the effect of blast-TBI and traumatic stress on retinal gene expression and assess the role of dietary deficiency of long chain ω-3 PUFAs on the vulnerability to these injury models. Linoleic acid was used as an independent variable to reflect the dietary increase in LA from 1 percent of energy (en%) to 8 en% present in the current western diets, and these custom LA diets were also devoid of long chain ω-3 PUFAs. Animals were exposed to a simulated blast overpressure wave followed by a weight drop head-concussion to induce TBI. Separate group of rats were subjected to traumatic stress by a forced underwater. Our findings showed that blast-TBI exposure, post 14 days, produced significant neuropathological changes such as axonal degeneration in the brain optic tracts from all the three diet groups, especially in rats fed the DHA-deprived 1 en% LA diet. Transcriptomic analysis showed that presence of DHA in the house chow diet prevented blast-induced disruption of neuronal plasticity by activating molecular networks like SNARE signaling, endocannabinoid pathway, and synaptic long-term depression when compared to DHA-deprived 8 en% LA diet group. Under traumatic stress, retinal synaptic function, neurovascular coupling, and opioid signaling mechanisms were dysregulated in rodents fed DHA-deficient diets (i.e., 8 en% LA and 1 en% LA), where reducing the levels of ω-6 linoleic acid from 8 en% to 1 en% was associated with increased neuronal plasticity and suppressed immune signaling. In conclusion, the findings of our study suggest that deprivation of long chain ω-3 PUFAs in the diet affects endocannabinoid-mediated neuronal plasticity, vascular function and inflammatory response that could influence the resistance of veterans to TBI and psychological trauma.